FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI DESA KUALU KECAMATAN TAMBANG KAMPAR - S, Putri Wulandini; Saputra, Roni (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Clean and Healthy Behavior/ PHBS is all health behavior that is done on the basis of awareness so that family members can help themselves in the health field. Health is a treasure that is priceless and to get health is willing to spend excessive funds. Based on the profile of Dinas Kesehatan Provinsi Riau the percentage of PHBS at home is 49,5%. Nevertheless, the implementation of PHBS in Rural areas remains a highlight and an ongoing program for the Government and District Health Offices. The purpose of this study was to find out